Non-muslim consumers' perception toward purchasing halal food products in Ampang, Selangor / Zahratie Mu'az - Mu'az, Zahratie (Faculty of Business and Management, 2018)
The rapid development in science and technology has left a great impact on the food processing industry. The halal concept is crucial because it includes other elements such as hygiene, ethics, values and food safety. As refer to the halal concept, it is used widely in all aspects of human life including for the food products, pharmaceuticals, cosmetics, health supplements and in the food ingredients. Thus, it is important for all Muslims to be more concern about the halal concept in their daily life. However, halal does not only concern Muslim, but non-Muslim as well. Based on The Star Online by Norkumala Awang (2016), the demand and dependency on halal food among Muslim and nonMuslim are high. Besides, the demand of halal product has been increasing since past few decades. However, many non-Muslim consumers yet consider halal food as an Islamic food. Therefore, it is important to conduct research on measuring the perception of non-Muslim consumers towards halal food. The objective of this research is to study the factors that influence the non-Muslim consumers' intention in purchasing halal food products. The factors that influence non-Muslim consumers' intention in purchasing halal food products include attitude, subjective norm and perceived behavioural control. The studies are involving 150 respondents who are readily available and convenient. The data has been obtained through close-ended questionnaires that will be randomly distributed to 150 non-Muslim consumers in Ampang, Selangor. This study expected that all independent variables which are attitude, subjective norm, perceived behavioural control have significant influence toward dependent variable which is nonMuslim consumers' intention to purchase halal food products in Ampang, Selangor. In addition, it is also important to identify which factor contributes most to the dependent variable.